1999
DOI: 10.1073/pnas.96.7.3562
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial protein engineering by incremental truncation

Abstract: We have developed a combinatorial approach, using incremental truncation libraries of overlapping N-and C-terminal gene fragments, that examines all possible bisection points within a given region of an enzyme that will allow the conversion of a monomeric enzyme into its functional heterodimer. This general method for enzyme bisection will have broad applications in the engineering of new catalytic functions through domain swapping and chemical synthesis of modified peptide fragments and in the study of enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
104
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 30 publications
3
104
0
1
Order By: Relevance
“…Earlier work has shown that folded hybrid domains can be created from homologous proteins (18)(19)(20). With our hybrid domains we were unable to detect any homologies between CspA and any of the donor proteins by sequence comparisons alone.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Earlier work has shown that folded hybrid domains can be created from homologous proteins (18)(19)(20). With our hybrid domains we were unable to detect any homologies between CspA and any of the donor proteins by sequence comparisons alone.…”
Section: Resultsmentioning
confidence: 75%
“…Experimentally, it has been shown that DNA shuffling of homologous genes can generate folded domains with improved properties (18)(19)(20). However, it is unlikely that such homologous recombinations can lead to the creation of entirely new protein folds, which are more likely to require the recombination of nonhomologous genes (3).…”
mentioning
confidence: 99%
“…Exchange of the C-terminal helix of the rat enzyme with the corresponding sequence from the human protein in clones RH-A5 and RH-F2 produced proteins that displayed 30-and 10-fold rate enhancements, respectively, relative to hGSTT1-1 but were nonetheless substantially less active than rGSTT2-2. Such reductions in catalytic rate relative to the most active parent are typical of chimeric enzymes derived from homologyindependent recombination (15,17,29).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several techniques for the combinatorial generation of protein chimeras in regions of low homology have been developed. These techniques include nonhomologous random recombination (15), sequence homologyindependent protein recombination (16), and incremental truncation for the creation of hybrid enzymes (ITCHY) and SCRATCHY (17,18). However, random nonhomologous recombination results in the creation of libraries containing a large number of out-of-frame or otherwise inactive clones.…”
mentioning
confidence: 99%
“…Artificial splitting of membrane proteins, which can form a catalytically active heterodimer complex, have been described earlier, [23][24][25] but such a conversion is not feasible in some cases, presumably due to insufficient assembly or improper folding of fragments. 26) Several split proteins were active only in the case of coexpression of the polypeptides in a restricted space in the cell, from a dicistronic operon on a single plasmid for example. 24) We also examined the effect of separate expression of the lysE24-N and lysE24-C regions from two plasmids in M. methylotrophus, and observed no enhancement of L-lysine production.…”
Section: Discussionmentioning
confidence: 99%